2022
DOI: 10.1208/s12248-022-00767-1
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Function of Extracellular Vesicles Derived from Immortalized Human Corneal Stromal Stem Cells: A Proof of Concept Study

Abstract: With significant advancement and development of extracellular vesicle (EV)-based therapies, there is a growing need to understand how their storage affects their physical and functional characteristics. EVs were isolated from the conditioned medium of a corneal stromal stem cell line (imCSSC) using Total Exosome isolation kit (TEI) and ultracentrifugation (UC) combined protocol. Purified EVs were stored at 4°C, − 80°C, room temperature (RT) after lyophilization with or without trehalose for 4 weeks. EVs stored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Retaining characteristic features of parent cells, EVs serve as pivotal mediators in intercellular communication. Instead of the time-intensive use of hucMSCs, along with the challenges of cryopreservation and the risk of vascular embolism, , human umbilical cord mesenchymal stromal cell-derived extracellular vesicles (hucMSC-EVs) present a potentially superior alternative owing to their real-time therapeutics, better in vivo distribution, and the negation of regulatory intricacies associated with traditional cell therapies. While numerous studies have confirmed the excellent therapeutic effects of hucMSC-EVs in promoting skin regeneration and repair, the specific molecular mechanisms and their impact on different types of cells involved in wound healing remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Retaining characteristic features of parent cells, EVs serve as pivotal mediators in intercellular communication. Instead of the time-intensive use of hucMSCs, along with the challenges of cryopreservation and the risk of vascular embolism, , human umbilical cord mesenchymal stromal cell-derived extracellular vesicles (hucMSC-EVs) present a potentially superior alternative owing to their real-time therapeutics, better in vivo distribution, and the negation of regulatory intricacies associated with traditional cell therapies. While numerous studies have confirmed the excellent therapeutic effects of hucMSC-EVs in promoting skin regeneration and repair, the specific molecular mechanisms and their impact on different types of cells involved in wound healing remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%